Biochar as a Carrier for Agrochemicals - Wan Roslina, Wan Yusof; Sumiyyah, Sabar; Enis Nadia, Md. Yusof.; Nur Shazwani, Abdul Mubarak (Springer Nature, 2024)
Biochar is a carbonaceous material with an adjustable surface structure and porosity. It can be produced by thermal decomposition from biomass under restricted oxygen conditions. Moreover, the functionalities of biochar can be enhanced through various modifications to meet the desired application, especially in agriculture. This chapter introduces the physicochemical properties of original biochar from different feedstocks and modification methods to improve biochar performances. Besides, recent studies on biochar application as a carrier for agrochemicals (fertilizers and pesticides) are discussed. Physical, chemical, and biological methods have been employed to improve the functionalities of biochar in terms of its particle sizes, surface area, pore size, adsorption, and desorption properties. Among all techniques, the chemical activation method has greater effectiveness and advantages. The recent developments of biochar as fertilizers and encapsulation material demonstrate that biochar can significantly improve crop productivity and soil properties. Moreover, the applications of biochar as a controlled release for different kinds of pesticides are mostly related to its ability in sorption and release properties.